2015
DOI: 10.1002/wrna.1282
|View full text |Cite
|
Sign up to set email alerts
|

The role of LARP1 in translation and beyond

Abstract: The LARP1 proteins form an evolutionarily homogeneous subgroup of the eukaryotic superfamily of La-Motif (LAM) containing factors. Members of the LARP1 family are found in most protists, fungi, plants, and animals. We review here evidence suggesting that LARP1 are key versatile messenger RNA (mRNA)-binding proteins involved in regulating important biological processes such as gametogenesis, embryogenesis, sex determination, and cell division in animals, as well as acclimation to stress in yeasts and plants. LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…LARP1 has been previously shown to be an mTORC1 effector and has been implicated as an important regulator of mRNA translation. [43][44][45][46] It is important to note that the serine 526 site found altered in our phosphoproteomics results is a different phosphorylation site than those previously proposed to be regulated by mTORC1. [47][48][49] We demonstrated an interaction between CDK9 and LARP1 through co-IP ( Figure 5B-C).…”
Section: Cdk9 Regulates Mrna Translation By Controlling Known Mtorc1 mentioning
confidence: 49%
“…LARP1 has been previously shown to be an mTORC1 effector and has been implicated as an important regulator of mRNA translation. [43][44][45][46] It is important to note that the serine 526 site found altered in our phosphoproteomics results is a different phosphorylation site than those previously proposed to be regulated by mTORC1. [47][48][49] We demonstrated an interaction between CDK9 and LARP1 through co-IP ( Figure 5B-C).…”
Section: Cdk9 Regulates Mrna Translation By Controlling Known Mtorc1 mentioning
confidence: 49%
“…However, the underlying molecular mechanisms that affect protein synthesis efficiency are largely unknown and in need of further research. A recent study revealed that heat stress can rapidly induce an mRNA degradation process where involving LARPs (La and related Proteins) (Deragon and Bousquet-Antonelli, 2015). Strikingly, mammalian LARP1 was implicated in translation regulation of TOP (5′-terminal oligopyrimidine tract)-containing mRNAs under the control of TOR (Tcherkezian et al, 2014); however, whether translation of many plant TOP-containing mRNAs (Dobrenel et al, 2016) depends on TOR remains to be identified.…”
Section: Tor Promotes Translation Reinitiation In Plantsmentioning
confidence: 99%
“…In this regard, while the anti-cancer cell and anti-cell proliferation effects of mTORC1 inhibition involve the downregulation of protein synthesis, possibly selectively, mTORC1 also impacts on other key pathways and proteins that regulate cell proliferation and survival. These include mTOR regulation by phosphorylation of the autophagy pathway (36) through the ULK1-mAtg13-FIP200 complex (37), the growth factor receptor bound protein 10 (Grb10) protein which blocks growth factor mitogenic signaling (38, 39), and the phosphorylation of mRNA binding proteins such as LARP1 that regulates cell division (40), among others. Consequently, if chemotherapy resistance can be reversed through mTOR inhibition, it might or might not directly involve mTORC1 phosphorylation of protein synthesis effectors S6K and 4E-BP1.…”
Section: Introductionmentioning
confidence: 99%